Hydrolytic Degradation and Assessment of Performance of PLA and PBS-Based Plastics Designed for Packaging Applications - Alberto Lagazzo; Cristina Moliner; Elisabetta Finocchio; Samantha Caputo; Elisabetta Arato (International Journal of Polymer Science)
Biopolymers based on poly(lactic acid) (PLA) and poly(butylene succinate) (PBS) reinforced with mineral fillers were studied in this work. The mechanical, spectroscopic (FTIR), and morphological (SEM) features of the raw samples were evaluated and compared with those of samples after immersion at diverse temperature (25°C, 37°C, and 70°C) in different degradation mediums (i.e., buffer solutions at pH=3, 5, and 7.5), simulating their applications as soft and rigid packaging in food containers and cosmetic packaging, respectively. The amount of absorbed water, Ms, increased with the increasing temperature as well as the diffusivity, D, indicating faster water diffusion rates. The pH slightly affected Ms whereas it produced contrary trends on D: acidic mediums were more aggressive for PLA-based materials (from 2.2∙108 cm2/s at pH=3 to 1∙108 cm2/s at pH=7.5 at 25°C) whereas higher pHs resulted in an increase on D for PBS-based ones (from 1∙108 cm2/s at pH=3 to 3.4∙108 cm2/s at pH=7.5 at 25°C). The effect of temperature on their mechanical performance, and thus on the aging/degradation of the materials, was predominant, as also evidenced by the morphological analysis, with the pH of the liquid media used to simulate the different packaging applications displaying only a marginal role. FTIR for both PLA and PBS-based materials indicated that the typical features of the polymers were not significantly changed at the different tested temperatures and no degradation products were detected at pH 3, 5, and 7.5. The obtained results showed the suitability of the PLA and PBS-based biocomposites for soft and rigid packaging applications where high temperatures are not required for long periods of time. These results will help in the designing of the new improved biocomposites to meet with the target objectives on their applications as packaging materials through the definition of the parameters to be tuned to tailor the bioplastics according to their specific needs.